2010
DOI: 10.1590/s0100-72032010001100006
|View full text |Cite
|
Sign up to set email alerts
|

Características ecográficas do corpo lúteo em gestações iniciais: morfologia e vascularização

Abstract: ResumoOBJETIVO: avaliar os aspectos morfológicos e vasculares do corpo lúteo (CL) por parâmetros ultrassonográficos durante a gestação inicial e sua associação com o abortamento. MÉTODOS: estudo de coorte, prospectivo com 90 gestantes entre 6 e 8 semanas mais 6 dias de gestação. Foram incluídas gestantes de baixo risco, sem doença sistêmica aguda ou crônica, e com concepção espontânea. Abstract PURPOSE: the purpose of this research was to evaluate the morphological aspects and vasculature of the corpus luteum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
2
0
2
Order By: Relevance
“…The major findings of our study were: a) the RI and PI were significantly lower in normal pregnancy group, while the D, V, VI, FI, and VFI were significantly higher; b) the AUC for ROC curve of RI among the two-dimensional parameters and FI among three-dimensional parameters were significantly higher; c) the joint indicator of RI and FI was not superior to individual RI or FI in the prediction of early intrauterine pregnancy outcomes. Our results were in accordance with the previous study (Pareja et al, 2010), when comparing the diameter and volume of the CL of normal pregnant women with those who aborted, found lower diameter and volume in cases of abortion. Many studies had demonstrated that RI and PI were significantly higher in patients of abortion (Applebaum, 1995; Durfee and Frates, 2015).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The major findings of our study were: a) the RI and PI were significantly lower in normal pregnancy group, while the D, V, VI, FI, and VFI were significantly higher; b) the AUC for ROC curve of RI among the two-dimensional parameters and FI among three-dimensional parameters were significantly higher; c) the joint indicator of RI and FI was not superior to individual RI or FI in the prediction of early intrauterine pregnancy outcomes. Our results were in accordance with the previous study (Pareja et al, 2010), when comparing the diameter and volume of the CL of normal pregnant women with those who aborted, found lower diameter and volume in cases of abortion. Many studies had demonstrated that RI and PI were significantly higher in patients of abortion (Applebaum, 1995; Durfee and Frates, 2015).…”
Section: Discussionsupporting
confidence: 94%
“…Transvaginal sonography has unique advantages in detecting the CL function by measuring its morphology, echo, size, volume, as well as evaluating the vascularity with color Doppler velocimetry. Previous researches did not reach an agreement about the morphology and echo of CL, which may attribute to individual difference (Pareja et al, 2010; Durfee and Frates, 2015). Therefore, we did not research the morphology and echo of CL in our study.…”
Section: Discussionmentioning
confidence: 82%
“…Color-Doppler ultrasonography was previously used in cows to evaluate the vascularity of follicle, CL, and conceptus (Myamoto et al 2005, Pareja et al 2010, Silva et al 2010). Therefore, since it is a non invasive technique and with reliable application, it is a useful tool to target new reproductive diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…Fonte: CNEN, 2019. A morfologia do corpo lúteo é frequentemente descrita como uma estrutura hipoecogênica (PAREJA et al, 2010). Cisto folicular (Figura 1A) é uma estrutura > 25 mm de diâmetro em um ovário que persiste por mais de 10 dias na ausência de um corpo lúteo sendo anecoico (BAITLESOV et al, 2007;FERNANDES et al, 2005).…”
Section: Introductionunclassified